1989
DOI: 10.1080/00365599.1989.11690431
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Oxalate and Calcium Absorption in Recurrent Renal Stone Formers and Healthy Subjects

Abstract: The fractional intestinal absorption of oxalate and calcium was investigated by isotope techniques in 20 normal subjects and in 12 idiopathic calcium oxalate stone formers. The greatest amount of 14C-oxalate was excreted during the first six hour period in controls as well as in stone formers. The stone formers had a greater intestinal uptake of oxalate (11 +/- 5.1%) than the controls (6.2 +/- 3.7%; p less than 0.01). There was no significant relationship between the fractional absorption of oxalate and the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Factors known to influence the percentage of this dietary oxalate that is absorbed include the availability of free calcium and magnesium ions that can complex with oxalate and decrease its rate of absorption, and the presence of free fats in the distal colon, which can form soaps with calcium and thereby increase concentration of free oxalate [20]. Recent [21,22] and older [23][24][25] studies also support the hypothesis that increased gastrointestinal absorption of oxalate due to factors independent of diet could mediate hyperoxaluria in a subgroup of calcium oxalate stone formers. There is evidence that specific energy-dependent transporters might mediate both net oxalate absorption, as well as oxalate excretion [26].…”
Section: Discussionmentioning
confidence: 99%
“…Factors known to influence the percentage of this dietary oxalate that is absorbed include the availability of free calcium and magnesium ions that can complex with oxalate and decrease its rate of absorption, and the presence of free fats in the distal colon, which can form soaps with calcium and thereby increase concentration of free oxalate [20]. Recent [21,22] and older [23][24][25] studies also support the hypothesis that increased gastrointestinal absorption of oxalate due to factors independent of diet could mediate hyperoxaluria in a subgroup of calcium oxalate stone formers. There is evidence that specific energy-dependent transporters might mediate both net oxalate absorption, as well as oxalate excretion [26].…”
Section: Discussionmentioning
confidence: 99%
“…The daily oxalate intake from a normal diet ranges between 80 and 100 mg (890 and 1,100 pmol/day). How ever, because most of the oxalate seems to be bound by calcium in the small intestine, which is then excreted as insoluble calcium oxalate complex, absorption usually does not exceed 10-20% of the amount present in food [15], Other investigators [16,17] have deter mined values of 8.3 or 6.2 ± 3.7% in normals and 14.6 or 11 ± 5.1% in stone formers. However, Heckers et al [18] believe that the contribution of dietary oxalate is generally underestimated: they indicated that with high intakes of oxalate-rich food, such as choco late, the urinary oxalate values can be in creased by up to 50%.…”
Section: The Origin Of Urinary Oxalatementioning
confidence: 99%
“…More commonly, however, higher concentrations of Ox in human fluids can cause a variety of pathological disorders, including hyperoxaluria, cardiomyopathy, cardiac conductance disorders, renal failure and, in particular, calcium oxalate (CaOx) nephrolithiasis [1][3]. Although oxalate can be absorbed by all segments of the intestinal tract, the large intestine appears to be where greatly enhanced oxalate absorption occurs in patients with enteric hyperoxaluria due to ileal disease [4], [5], chronic inflammatory bowel disease [6], as well as fat malabsorption, steatorrhea and sprue [5]. Enteric hyperoxaluria is also a well-documented entity observed in gastrointestinal diseases, such as colitis or Crohn's disease or following ileal resection in jejuno-ileal bypass surgery, and now certain bariatric surgeries for obesity [6][10].…”
Section: Introductionmentioning
confidence: 99%